REVIEW OF THE ENERGY LAW OF THE REPUBLIC OF UZBEKISTAN - IKHTIYOR, BEKOV (International Journal of Psychosocial Rehabilitation, 2020)
the article is devoted to the legal analysis of approaches to the understanding of energy law. The author analyzed the legal acts regulating relations related to energy (fuel and energy complex) in the Republic of Uzbekistan and the peculiarities of their legal regulation in various legal systems. In the presented work the author considered the processes of historical evolution and formation of the concept of energy law. At the same time, the paper offers conclusions about the features of the integration of methods for energy regulation in the Republic of Uzbekistan, new types of agreements and standards in the energy sector, as well as conclusions about the prospects and directions of sustainable development of the principles of legal regulation of energy.The author in the study proceeds from economic and socio-cultural approaches to law and the state. Taking into account the opinions of the predecessors of this direction in science, in particular: opinions on the significance of the subject matter of the Australian scientist Adrian Bradbrew, representative of the modern theory of energy law: Energy itself has an “all-consuming social importance.”3Considering the socio-historical retrospective of the subject: the term was first defined in the study as–“Energy is the name given to an effect (phenomenon) or group of natural phenomena (phenomena) demonstrated (shown) by various substances (materials), as well as the phenomena themselves.”4Given the importance of rational legal regulation for the world community the subject of the study: schemes for trading quotas on harmful emissions as one of the market instruments of regulation.5The material of the article shows the permissible limits of independence of the energy sector of the Republic of Uzbekistan. Review of the ongoing processes of globalization of the country's economy, with the convergence of national legal systems and unification of law in the field of energy regulation and also, about the issues related to the problems arising from these changes in this area.